High-performance OCA optical adhesive for bonding curved screens and preparation method thereof
By introducing unsaturated double bond functionalized POSS and other monomers into OCA optical glue, the polymer cross-linking network is optimized, and the problem of insufficient mechanical tensile and filling performance of OCA optical glue in curved screen bonding is solved. The OCA optical glue with high performance, stability and long life is achieved, avoiding bubble rebound and improving product reliability and stability.
Patent Information
- Application Number
- CN202311654848.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-12-05
AI Technical Summary
The existing OCA optical glue has insufficient mechanical tensile performance and filling performance in curved screen bonding applications, which are prone to poor phenomena such as bubble rebound, and is poor in stability and is not resistant to storage, making it difficult to meet the needs of high performance and long life.
Unsaturated double bond functionalized POSS is used as polymerizable monomer, and OCA optical glue is prepared through UV polymerization with alkyl acrylate, polar acrylate, and high Tg acrylate to optimize the polymer cross-linking network structure and enhance the integration of the adhesive film. Properties, including combinations of alkyl acrylates, polar acrylates, unsaturated double bond functionalized POSS, high Tg acrylates, chain transfer agents, photoinitiators, crosslinking agents and coupling agents, by UV polymerization and coating Process to prepare high-performance OCA optical glue.
It realizes excellent fitting and filling performance, good fluidity and bonding performance of OCA optical adhesive, avoids bubble rebound, improves product stability and service life, and has excellent optical performance and yellowing resistance, suitable for different environments Applications under.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical adhesives, and in particular to a high-performance OCA optical adhesive for bonding curved screens and a preparation method thereof. Background Art
[0002] Benefiting from the rapid development of science and technology, consumer electronic products are developing faster and faster. These consumer electronic products are inseparable from touch screens. The extensive use of touch screens heralds the arrival of the touch display era. The touch display era has quietly changed and enriched our daily lives. Modern people's daily lives are inseparable from touch screens. In particular, the increasingly popular curved screen technology has greatly improved people's visual experience. In the assembly process of curved touch screens, OCA optical adhesive film is required to bond special flexible curved screens and OLEDs. The curvature of the curved surface greatly increases the seamless bonding between the flexible screen and the OLED. It can be seen that it is particularly important to develop OCA optical adhesives for curved screen bonding with good comprehensive performance and performance stability.
[0003] OCA optical adhesive has the advantages of being colorless and transparent, with a light transmittance of more than 90%, high adhesion, and small shrinkage after curing. It is used to fill the gap between the touch layer and the screen, and mainly plays the role of bonding, light transmission, display enhancement, and buffering. In order to meet the effective filling of the curved position of the screen and the filling of the ink step difference, OCA not only requires excellent bonding and filling performance, adhesion and mechanical tensile properties, but also does not have adverse phenomena such as static bubble rebound and reliability test bubble rebound. At present, conventional OCA optical adhesive products on the market do not have excellent mechanical tensile properties and filling properties. It is difficult to meet the effective bonding of the curved position and the filling of the ink step difference, and it is easy to have adverse phenomena such as bubble rebound; and the stability is poor and it is not resistant to storage.
[0004] In order to solve the above problems, the Chinese invention patent with application number 202211587449.3 discloses an OCA optical adhesive for 3D curved screens, and its preparation method and application. The OCA optical adhesive for 3D curved screens is mainly made of the following components by weight: 100 parts of oligomer, 0.1-1 parts of the first photoinitiator, 0.5-1 parts of the thermal crosslinking agent, 1-5 parts of the functional additive and 0.1-1 parts of the silane coupling agent; the oligomer is mainly made of the following components by weight: 30-85 parts of methoxy polyethylene glycol (550) monomethacrylate, 10-40 parts of tetrahydrofuran acrylate, 5-20 parts of hydroxyethyl acrylate, 10-30 parts of glycidyl methacrylate, 2-10 parts of 1,6-hexanediol diacrylate and 0.1-1.5 parts of the second photoinitiator. The OCA optical adhesive of the invention has high filling properties, can prevent bubble rebound, and has high bonding properties. However, the use of thermal cross-linking curing in the later stage of curing will affect the efficiency and yield rate in actual production.
[0005] Therefore, the development of a high-performance OCA optical adhesive for bonding curved screens with excellent heat resistance, optical transparency, mechanical properties, good performance stability, and long service life, and a preparation method thereof, meets market demand, has broad market value and application prospects, and is of great significance to promoting the further development and application of OCA optical adhesives. Summary of the invention
[0006] The main purpose of the present invention is to provide a high-performance OCA optical adhesive for bonding curved screens and a preparation method thereof. Unsaturated double-bond functionalized POSS is used as a polymerizable monomer, and (meth) alkyl acrylate, polar (meth) acrylate, and high Tg (meth) acrylate monomers are polymerized by UV, and coated to prepare the OCA optical adhesive; the introduction of the POSS group can optimize the polymer cross-linking network structure in the final adhesive film, comprehensively improve the comprehensive performance of the OCA optical adhesive, give it outstanding light transmittance and yellowing resistance, meet the requirements of the reliability test, and ensure the reliability of the product in different environments.
[0007] To achieve the above purpose, the present invention provides a high-performance OCA optical adhesive for bonding curved screens, characterized in that it is made of the following raw materials in parts by weight: 40-60 parts of alkyl acrylate, 5-25 parts of polar acrylate, 0.1-4 parts of unsaturated double bond functionalized POSS, 15-45 parts of high Tg acrylate, 0.05-1 parts of chain transfer agent, 0.01-1.5 parts of photoinitiator, 0.05-1 parts of cross-linking agent, and 0.01-0.8 parts of coupling agent.
[0008] Preferably, the alkyl acrylate is one or more of n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, n-octyl acrylate, n-octyl methacrylate, dodecyl acrylate, dodecyl methacrylate, isononyl acrylate, and isodecyl acrylate.
[0009] Preferably, the polar acrylic ester is one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, acrylamide, methacrylamide, N-hydroxyethyl acrylamide, N-vinyl pyrrolidone, 4-acryloylmorpholine, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, and N,N-dimethylacrylamide.
[0010] Preferably, the unsaturated double bond functionalized POSS is an unsaturated double bond functionalized caged silsesquioxane, selected from one or more of acryloxypropyl POSS, methacryloxypropyl POSS, and vinyl POSS.
[0011] Preferably, the high Tg acrylate is one or more of isobornyl acrylate, isobornyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, and 3,3,5-trimethylcyclohexyl acrylate.
[0012] Preferably, the chain transfer agent is one or more of dodecyl mercaptan, isooctyl thioglycolate, 2-mercaptoethanol, isooctyl 3-mercaptopropionate, and pentaerythritol tetrakis (3-mercaptobutyrate).
[0013] Preferably, the photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 4-acryloylhydroxybenzoic acid benzophenone, and benzophenone.
[0014] Preferably, the crosslinking agent is one or more of 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and ethoxylated trimethylolpropane triacrylate.
[0015] Preferably, the coupling agent is one or more of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0016] The present invention also provides a method for preparing the high-performance OCA optical adhesive for bonding the curved screen, comprising the following steps:
[0017] Step S1, adding alkyl acrylate, polar acrylate, unsaturated double bond functionalized POSS, high Tg acrylate, chain transfer agent and photoinitiator into a reaction container, stirring and mixing evenly, and performing nitrogen replacement, and polymerizing by UV radiation at room temperature to obtain an acrylic prepolymer;
[0018] Step S2, then adding a coupling agent and a cross-linking agent to the above materials, stirring evenly, and filtering with a 200-500 mesh filter bag to obtain an optical adhesive;
[0019] Step S3: evenly apply the optical adhesive between the heavy release film and the light release film, and irradiate with UV to finally obtain the OCA optical adhesive.
[0020] Preferably, the normal temperature condition in step S1 is an ambient temperature of 20-30°C.
[0021] Preferably, the light source used for UV radiation in step S1 is a 395nm LED lamp.
[0022] Preferably, the light source used for UV radiation in step S3 is a low-pressure mercury lamp.
[0023] Preferably, the thickness of the OCA optical adhesive in step S3 is 100-150 μm.
[0024] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0025] (1) The OCA optical adhesive prepared by the present invention has excellent bonding and filling performance, good fluidity under high temperature and high pressure, and can effectively fill and bond the screen. At the same time, it can effectively wet and fill different ink step differences, fully ensuring the bonding yield.
[0026] (2) The OCA optical adhesive prepared by the present invention has excellent room temperature and high temperature bonding properties and mechanical tensile properties, has sufficient strength to support the curved surface, and will not have undesirable phenomena such as static bubble rebound and reliability test bubble rebound, thereby ensuring the reliability of the product in different environments and comprehensively improving the stability and service life of the terminal product.
[0027] (3) The OCA optical adhesive of the present invention has excellent optical properties and yellowing resistance.
[0028] (4) The OCA optical adhesive of the present invention is obtained by bulk UV polymerization, which has a simple process, short time consumption, does not use solvents, is safe and environmentally friendly, and is conducive to industrial production. DETAILED DESCRIPTION
[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0030] The composition of the OCA optical adhesive of this embodiment is shown in the following table:
[0031]
[0032] (1) Add 2-ethylhexyl acrylate, hydroxyethyl acrylate, methacryloyloxypropyl POSS, cyclohexyl acrylate, dodecyl mercaptan, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide into a reaction kettle equipped with a thermometer and a stirring device, stir and mix evenly, bubble nitrogen for 30 minutes, and then polymerize by radiation with an LED lamp at 25°C. The reaction is terminated after the temperature is raised by 25°C to obtain an acrylic prepolymer.
[0033] (2) Add 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 4-acryloylhydroxybenzoic acid benzophenone, 1,6-hexanediol diacrylate and KH560 to the above materials, stir well and filter with a 400-mesh filter bag to obtain an optical adhesive.
[0034] (3) After vacuum degassing, the optical adhesive was uniformly coated between the heavy release film and the light release film, and cured by irradiation with a low-pressure mercury lamp for 3.5 minutes to obtain a 100 μm OCA optical adhesive. Example 2
[0035] The composition of the OCA optical adhesive of this embodiment is shown in the following table:
[0036]
[0037] (1) Add 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, hydroxyethyl acrylate, acryloyloxypropyl POSS, acrylamide, isobornyl acrylate, dodecyl mercaptan, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide into a reactor equipped with a thermometer and a stirring device, stir and mix evenly, bubble nitrogen for 30 minutes, and then polymerize by LED light radiation at 25°C. Raise the temperature by 40°C to terminate the reaction to obtain an acrylic acid prepolymer.
[0038] (2) Add 1-hydroxycyclohexyl phenyl ketone, 4-acryloylhydroxybenzoic acid benzophenone, 1,6-hexanediol diacrylate and KH560 to the above materials, stir well and filter with a 500-mesh filter bag to obtain an optical adhesive.
[0039] (3) After vacuum degassing, the optical adhesive was uniformly coated between the heavy release film and the light release film, and cured by irradiation with a low-pressure mercury lamp for 3.2 minutes to obtain a 150 μm OCA optical adhesive. Example 3
[0040] The composition of the OCA optical adhesive of this embodiment is shown in the following table:
[0041]
[0042] (1) n-Octyl acrylate, hydroxybutyl acrylate, vinyl POSS, 3,3,5-trimethylcyclohexyl acrylate, pentaerythritol tetrakis (3-mercaptobutyrate), and phenylbis (2,4,6-trimethylbenzoyl) phosphine oxide were added into a reaction kettle equipped with a thermometer and a stirring device, stirred and mixed evenly, and nitrogen was bubbled for 30 minutes. Then, the mixture was polymerized by radiation from an LED lamp at 25°C, and the reaction was terminated after the temperature was raised to 36°C to obtain an acrylic acid prepolymer.
[0043] (2) Add 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 4-acryloylhydroxybenzoic acid benzophenone, benzophenone, tripropylene glycol diacrylate and KH570 to the above materials, stir well and filter with a 500-mesh filter bag to obtain an optical adhesive.
[0044] (3) After vacuum degassing, the optical adhesive was uniformly coated between the heavy release film and the light release film, and cured by irradiation with a low-pressure mercury lamp for 4 minutes to obtain a 125 μm OCA optical adhesive. Example 4
[0045] The composition of the OCA optical adhesive of this embodiment is shown in the following table:
[0046]
[0047] (1) Add 2-ethylhexyl acrylate, dodecyl acrylate, hydroxypropyl acrylate, acryloyloxypropyl POSS, isobornyl acrylate, isooctyl 3-mercaptopropionate and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide into a reactor equipped with a thermometer and a stirring device, stir and mix evenly, bubble nitrogen for 30 minutes, and then polymerize by LED light radiation at 25°C. The reaction is terminated after the temperature is raised by 15°C to obtain an acrylic acid prepolymer.
[0048] (2) Add 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 4-acryloylhydroxybenzoic acid benzophenone, 1,6-hexanediol diacrylate and KH560 to the above materials, stir well and filter with a 500-mesh filter bag to obtain an optical adhesive.
[0049] (3) After vacuum degassing, the optical adhesive was uniformly coated between the heavy release film and the light release film, and cured by irradiation with a low-pressure mercury lamp for 5 minutes to obtain a 150 μm OCA optical adhesive. Example 5
[0050] The composition of the OCA optical adhesive of this embodiment is shown in the following table:
[0051]
[0052] (1) 2-Ethylhexyl methacrylate, isononyl acrylate, hydroxyethyl acrylate, acryloyloxypropyl POSS, isobornyl acrylate, dodecyl mercaptan, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide were added into a reaction kettle equipped with a thermometer and a stirring device, stirred and mixed evenly, and nitrogen was bubbled for 30 minutes. Then, the mixture was polymerized by radiation from an LED lamp at 25°C, and the reaction was terminated after the temperature was raised to 47°C to obtain an acrylic acid prepolymer.
[0053] (2) Add 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 4-acryloylhydroxybenzoic acid benzophenone, ethoxylated trimethylolpropane triacrylate and KH550 to the above materials, stir well and filter with a 400-mesh filter bag to obtain an optical adhesive.
[0054] (3) After vacuum degassing, the optical adhesive was uniformly coated between the heavy release film and the light release film, and cured by irradiation with a low-pressure mercury lamp for 5 minutes to obtain a 125 μm OCA optical adhesive.
[0055] Comparative Example 1
[0056] The composition of the OCA optical adhesive of this comparative example is shown in the following table:
[0057]
[0058] (1) Add 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, hydroxyethyl acrylate, acrylamide, isobornyl acrylate, dodecyl mercaptan, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide into a reaction kettle equipped with a thermometer and a stirring device, stir and mix evenly, bubble nitrogen for 30 minutes, and then polymerize by radiation with an LED lamp at 25°C. Raise the temperature by 40°C to terminate the reaction to obtain an acrylic acid prepolymer.
[0059] (2) Add 1-hydroxycyclohexyl phenyl ketone, 4-acryloylhydroxybenzoic acid benzophenone, 1,6-hexanediol diacrylate and KH560 to the above materials, stir well and filter with a 500-mesh filter bag to obtain an optical adhesive.
[0060] (3) After vacuum degassing, the optical adhesive was uniformly coated between the heavy release film and the light release film, and cured by irradiation with a low-pressure mercury lamp for 3.2 minutes to obtain a 150 μm OCA optical adhesive.
[0061] Effect Example 1
[0062] The physical properties of the OCA optical adhesives prepared in Examples 1-5 of the present invention and Comparative Example 1 were tested. The testing methods are listed as follows:
[0063] Gel fraction: Weigh a sample with mass A, soak it in ethyl acetate for 24 hours, filter it with a 200-mesh filter (filter mass B), bake it at 120°C for 1 hour, and weigh it, recorded as C. Gel fraction % = (CB) / A*100%.
[0064] Optical properties: Cut OCA into 50mm*50mm strips, remove the light release film, attach it to optical quartz glass, remove the heavy release film, and test the optical properties of the series using a spectrophotometer in a constant temperature and humidity room.
[0065] Adhesion: Cut OCA into 25mm*15cm strips, remove the light release film, apply 50μm PET, then remove the heavy film, and stick it to a transparent glass plate. Roll it back and forth three times with a 2Kg roller. After standing in a constant temperature and humidity room for 20 minutes, use a tensile machine at a speed of 300mm / min, 180o Direction peel test sample.
[0066] Dielectric constant: stack the OCA onto a sample with a thickness of more than 500μm (actual thickness T), then remove the light release film, laminate it onto a metal electrode (area S), and then laminate another metal electrode. Clamp the two metal electrodes with a clip, adjust the test frequency, record the inherent capacitance (Cp) value, and calculate the dielectric constant = Cp×T / (8.854×S), where 8.854 is a constant.
[0067] Stretching: Cut the OCA optical adhesive into a width of 6.5cm, remove the release film and stack it into samples with a thickness of 0.7mm, then cut it into 25mm width, tear off the release film on one end of the sample and use invisible tape to cut an effective length of 25mm, tear off the release film on the other side, stick the invisible tape into a handle, fix it on the fixture and use a tensile machine for testing.
[0068] The storage modulus and loss factor tanδ were measured using a TA hybrid rheometer DHR-2. The OCA optical adhesive was laminated and stacked to a sample with a thickness of 1mm±0.05mm without wrinkles or bubbles. A circular sample with a diameter of 0.8mm was made using a fixture and tested according to the operating procedures. Test conditions: 1Hz, 0.1% strain. Creep recovery test conditions: 40kPa, 25℃, creep 600s, recovery 600s, test results are shown in Table 1.
[0069] Table 1
[0070]
[0071] From the data in Table 1, it can be seen that the OCA optical adhesive prepared by the present invention has excellent adhesion and mechanical tensile properties. Tanδ (50℃) and tanδ (100℃) are between 0.6-0.8, which can ensure that OCA has good fluidity under high temperature and high pressure, effectively wet and fill the screen and ink step difference, and fully ensure the bonding yield. At the same time, the room temperature storage modulus is greater than 155000Pa, which can effectively ensure that there is sufficient strength to support the curved surface during the bonding production process to avoid bubble rebound.
[0072] The physical properties of OCA optical adhesive after UV curing are shown in Table 2. UV curing conditions: high pressure mercury lamp, energy> 3000mJ / cm 2 ; LED light (365nm), energy>4000mj / cm 2 Here, UV curing is adopted under high pressure mercury lamp, with energy of 3500mJ / cm 2 .
[0073] Table 2
[0074]
[0075] From the data in Table 2, it can be seen that the OCA optical adhesive prepared by the present invention exhibits excellent optical and mechanical properties after UV curing. The gel fraction after UV curing is greater than 80%, indicating that the colloid curing reaction is sufficient, and the storage modulus is greater than 200000Pa, and the colloid can effectively prevent bubble rebound.
[0076] Curved surface bonding and reliability test: tear off the light OCA optical adhesive film and attach it to the upper polarized light of the OLED module, tear off the heavy film on the other side, and bond it to the curved cover with a 30μm ink step difference on all sides, with a bonding pressure of 0.35MPa, and then degassing and bonding at 50℃ / 0.5MPa / 25min, and observe the bubbles on the edge of the ink. Finally, UV curing is performed under a high-pressure mercury lamp with an energy of 3500mj / cm2. Observe again whether there are bubbles rebounding. The samples after the above simulated bonding were placed in the hot and cold shock (-40℃*30min / 85℃*30min, 200 cycles), high temperature and high humidity (85℃*85%RH, 500h), high temperature (85℃, 500h), low temperature (-40℃, 500h), QUV (0.63W / m2, 340nm, 500h) test box, 20 pieces were placed in each condition, and after the end, they were taken out for observation. If there is no bubble rebound, no whitening, no yellowing, no warping and debonding, it is OK; if any piece has the above defects, it is NG. The test results are shown in Table 3.
[0077] From the test results in Table 3, it can be seen that the OCA optical adhesive prepared by the present invention exhibits excellent aging performance, with no bubble rebound, no whitening, no yellowing, and no warping and debonding. The reliability of the product in different environments is guaranteed, and the stability and service life of the terminal product are comprehensively improved. However, one piece of comparative example 1 had bubble re-bounce under high temperature and high humidity and QUV aging conditions.
[0078] Table 3
[0079]
[0080] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-performance OCA optical adhesive for bonding curved screens, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of alkyl acrylate, 5-25 parts of polar acrylate, 0.1-4 parts of unsaturated double bond functionalized POSS, 15-45 parts of high Tg acrylate, 0.05-1 parts of chain transfer agent, 0.01-1.5 parts of photoinitiator, 0.05-1 parts of crosslinking agent and 0.01-0.8 parts of coupling agent; the high Tg acrylate is one or more of isobornyl acrylate, isobornyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate and 3,3,5-trimethylcyclohexyl acrylate; the chain transfer agent is one or more of dodecyl mercaptan, isooctyl thioglycolate, 2-mercaptoethanol, isooctyl 3-mercaptopropionate and pentaerythritol tetrakis (3-mercaptobutyrate); The method for preparing the high-performance OCA optical adhesive for bonding the curved screen comprises the following steps: Step S1, adding alkyl acrylate, polar acrylate, unsaturated double bond functionalized POSS, high Tg acrylate, chain transfer agent and photoinitiator into a reaction container, stirring and mixing evenly, and performing nitrogen replacement, and polymerizing by UV radiation at room temperature to obtain an acrylic prepolymer; Step S2, then adding a coupling agent and a cross-linking agent to the above materials, stirring evenly, and filtering with a 200-500 mesh filter bag to obtain an optical adhesive; Step S3: evenly apply the optical adhesive between the heavy release film and the light release film, and irradiate with UV to finally obtain the OCA optical adhesive.
2. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The alkyl acrylate is one or more of n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, n-octyl acrylate, n-octyl methacrylate, dodecyl acrylate, dodecyl methacrylate, isononyl acrylate, and isodecyl acrylate.
3. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The polar acrylic ester is one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, acrylamide, methacrylamide, N-hydroxyethyl acrylamide, N-vinyl pyrrolidone, 4-acryloylmorpholine, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, and N,N-dimethylacrylamide.
4. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The unsaturated double-bond functionalized POSS is one or more of acryloyloxypropyl POSS, methacryloyloxypropyl POSS, and vinyl POSS.
5. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 4-acryloylhydroxybenzoic acid benzophenone, and benzophenone.
6. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The crosslinking agent is one or more of 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and ethoxylated trimethylolpropane triacrylate; the coupling agent is one or more of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
7. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The normal temperature condition in step S1 is an ambient temperature of 20-30° C.; the light source used for UV radiation in step S1 is a 395 nm LED lamp.
8. The high-performance OCA optical adhesive for bonding curved screens according to claim 1, characterized in that: The light source used for UV radiation in step S3 is a low-pressure mercury lamp; the thickness of the OCA optical adhesive in step S3 is 100-150 μm.
Citation Information
Patent Citations
OCA (optical clear adhesive) for 3D (three-dimensional) curved screen as well as preparation method and application of OCA
CN115678440A
Zero-VOC (Volatile Organic Compounds) photo-polymer acrylate pressure-sensitive adhesive composition and preparation method thereof
CN103396741A
OCA optical glue for curved screen, glue film and preparation method of OCA optical glue
CN115124928A
Acrylic copolymer and adhesive composition
KR1020140136163A
Nail coatings having enhanced adhesion
US20160067164A1
